Transactions on Pattern Languages of Programming I - Noble, James; Johnson, Ralph (Transactions on Pattern Languages of Programming, 2009)
The Transactions on Pattern Languages of Programming subline aims to publish papers on patterns and pattern languages as applied to software design, development, and use, throughout all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The primary focus of this LNCS Transactions subline is on patterns, pattern collections, and pattern languages themselves. The journal also includes reviews, survey articles, criticisms of patterns and pattern languages, as well as other research on patterns and pattern languages. This book, the first volume in the Transactions on Pattern Languages of Programming series, presents eight papers that have been through a careful peer review process involving both pattern experts and domain experts, by researchers and practitioners. The papers cover a wide range of topics, from the architectural design of large-scale systems down to very detailed design for microcontroller-based embedded systems. The first paper presents a substantial pattern language for constructing an important part of an integrated development environment. The following papers present patterns for batching requests in client-server systems; graceful degradation to handle errors and exceptions; and accurate timing delays. Two papers present related patterns that address aspects of service-oriented architectures, considering synchronization and workflow integration. Finally, the last two papers show how patterns can be combined into systems and then used to document those systems' designs.